2016
DOI: 10.2174/1381612822666151214105439
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Catabolites and Migraine

Abstract: Abstract:Migraine is a highly disabling neurological condition affecting around 15% of the population worldwide.Decades of intensive research shed some light on diseases pathomechanism, but information is still missing about the initiation of the attack. In the past century, serotonin emerged as the main target of both basic and therapeutic research. As a result, the triptans, the only approved migraine specific drugs were developed. The involvement of glutamatergic mechanism in migraine headache development s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 135 publications
0
7
0
Order By: Relevance
“…It has been proposed that niacin might exert beneficial effects by acting at both central and peripheral levels; in particular, it efficaciously dilates intracranial vessels and subsequently contracts extracranial vessels, favoring, in parallel, the release of compounds leading to peripheral vasodilation and cutaneous flushing. Taking into account that plasma content of serotonin inversely correlates with headache onset, niacin acts, at the central level, by increasing Trp-dependent synthesis of serotonin, via feedback inhibition of the KP [194]. At the peripheral level, pharmacological doses of nicotinic acid increase skin biosynthesis of prostaglandin D2 [195] and the plasma content of its by-product 9a,11b-PGF2, in healthy volunteers [196].…”
Section: Other Neurological Diseasesmentioning
confidence: 99%
“…It has been proposed that niacin might exert beneficial effects by acting at both central and peripheral levels; in particular, it efficaciously dilates intracranial vessels and subsequently contracts extracranial vessels, favoring, in parallel, the release of compounds leading to peripheral vasodilation and cutaneous flushing. Taking into account that plasma content of serotonin inversely correlates with headache onset, niacin acts, at the central level, by increasing Trp-dependent synthesis of serotonin, via feedback inhibition of the KP [194]. At the peripheral level, pharmacological doses of nicotinic acid increase skin biosynthesis of prostaglandin D2 [195] and the plasma content of its by-product 9a,11b-PGF2, in healthy volunteers [196].…”
Section: Other Neurological Diseasesmentioning
confidence: 99%
“…It has been already demonstrated that the level of KYNA and some other KP metabolites are altered in migraine and cluster headache patients as well: there are significant reductions in the serum levels of KYN, KYNA, 3-hydroxy-kynurenine, 3-hydroxyanthranilic acid and quinolinic acid, whereas concentrations of TRP and anthranilic acid were significantly increased [72,73]. KYNA as an endogenous NMDA receptor antagonist, is a molecule of interest for CNS drug development in case of several neurological conditions [74], but due to its poor ability to cross the blood-brain barrier (BBB) and its rapid clearance from the body [75], its application for most CNS-related alterations is limited, and therefore several KYNA analogs were synthetized [76][77][78][79]. However, the first order neuron of pain processing is located outside the BBB [80], so KYNA itself may have therapeutic potential as well.…”
Section: Tryptophan Metabolism and Painmentioning
confidence: 99%
“…It has been already demonstrated that the level of KYNA and some other KP metabolites are altered in migraine and cluster headache patients as well: there are significant reductions in the serum levels of KYN, KYNA, 3-hydroxy-kynurenine, 3-hydroxy-anthranilic acid and quinolinic acid, whereas concentrations of TRP and anthranilic acid were significantly increased [72,73]. KYNA as an endogenous NMDA receptor antagonist, is a molecule of interest for CNS drug development in case of several neurological conditions [74], but due to its poor ability to cross the blood-brain barrier (BBB) and its rapid clearance from the body [75], its application for most CNS-related alterations is limited, and therefore several KYNA analogs were synthetized [76][77][78][79]. However, the first order neuron of pain processing is located outside the BBB [80], so KYNA itself may have therapeutic potential as well.…”
Section: Tryptophan Metabolism and Migrainementioning
confidence: 99%